Locally‐Strain‐Induced Heavy‐Hole‐Band Splitting Observed in Mobility Spectrum of p‐Type InAs Grown on GaAs. Issue 4 (14th February 2020) - Wróbel, Jarosław; Umana-Membreno, Gilberto A.; Boguski, Jacek; Sztenkiel, Dariusz; Michałowski, Paweł Piotr; Martyniuk, Piotr; Faraone, Lorenzo; Wróbel, Jerzy; Rogalski, Antoni
Abstract : High‐quality Be‐doped InAs layer grown by molecular beam epitaxy on GaAs substrate has been examined via magnetotransport measurements and high‐resolution quantitative mobility spectrum analysis (HR‐QMSA) in the range of 5–300 K and up to 15 T magnetic field. The results show four‐channel conductivity and essential splitting of the most populated hole‐like channel below 55 K. It is concluded that origin of such effect results from the locally strain‐induced interlayer, which direct observation is difficult or impossible via alternative techniques. Based on the magnetotransport data analysis, the multilayer model is proposed, which is implemented into nextnano simulation, giving the proof of the argumentation correctness. These results indicate potential usefulness of HR‐QMSA technique even in the degeneration statistic regime. Abstract : The results of magnetotransport measurements and mobility spectrum analysis calculations show that multichannel conductivity occurs in the InAs:Be layer on GaAs substrate. Interestingly, heavy‐hole‐conductivity‐channel splitting, which origins from the shear strain on InAs/GaAs interface, leads to lowering of the average mobility in the sample.